Expanding the phenotype and metabolic basis of ATP6AP2-congenital disorder of glycosylation in a Chinese patient with a novel variant c.185G>A (p.Gly62Glu) - Fang, Yuan; Wang, Yi-Zhen; Chen, Lian; Xie, Xin-Bao (Frontiers in Genetics, 2023)
A rare X-linked hereditary condition known as ATP6AP2-congenital disorder of glycosylation (ATP6AP2-CDG) is caused by pathogenic variants in ATP6AP2, resulting in autophagic misregulation with reduced siganling of mammalian target of rapamycin (mTOR) that clinically presents with aberrant protein glycosylation, hepatosteatosis, immunodeficiency, cutis laxa, and psychomotor dysfunction. To date, only two missense mutations have been reported in three patients from two unrelated families. In order to extend the profiles of phenotype and genotype associated with ATP6AP2-CDG, we assessed the clinical history, whole exome sequencing (WES), and liver histology as well as immunohistochemistry in a Chinese patient, and performed quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting and untargeted metabolomics in genetic exogenously constructed cells. The 11-month-old Chinese boy presented with recurrent jaundice, cutis laxa, cirrhosis, growth retardation, coagulopathy, anemia, and cardiomegaly, and underwent liver transplantation. A novel mutation, c.185G>A (p.Gly62Glu), was identified in exon 3 of ATP6AP2. The expression of ATP6AP2 was observed to remain unchanged in the liver sample of the patient as well as in HEK293T cells harboring the p.Gly62Glu. This missense mutation was found to disregulate autophagy and mTOR signaling.Moreover, metabolomics analysis revealed that the exogenously introduced Gly62Glu mutant resulted in the downregulation of numerous metabolites involved in lipid metabolism pathway. Thereby, this study may enable a more detailed exploration of its precise pathogenesis and potential therapeutic interventions.